Low-carbon recycled brick and preparation method thereof
Patent Information
- Application Number
- CN202611102690.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的目的在于提出一种低碳再生砖及其制备方法,解决了装修垃圾有机物去除困难、再生骨料强度低、能耗高、碳排放大等问题,实现了装修垃圾的高效资源化利用和低碳绿色生产
1、 本发明通过齿辊破与平辊破的分级破碎组合,实现了装修垃圾中有机物与无机物的高效分离,再生砂粉含杂率显著降低;装修垃圾中的脆性无机物被有效破碎成砂粉状,而柔性有机物(如木条、塑料、布匹)保持原状或被撕裂成较大片状,极大降低了“筛分除杂”的难度。
Smart Images

Figure CN122916600A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a low-carbon recycled brick and its preparation method. Background Technology
[0002] Construction waste is complex in composition, typically containing inorganic materials such as concrete blocks, red bricks, ceramics, and glass, as well as organic debris such as plastics, wood strips, fabrics, and packaging materials. Currently, the disposal of construction waste mostly involves landfilling or simple incineration, which not only occupies large amounts of land and damages the environment but also prevents the rational utilization of inorganic resources, leading to resource waste. Therefore, the resource utilization of construction waste to produce recycled building materials, turning waste into treasure, is an urgent problem to be solved in the field of construction waste management.
[0003] Currently, the main technical defects in the recycling technology of construction waste are as follows: First, dissociation and separation are difficult. Traditional jaw crushers or hammer crushers can cause organic matter to be compressed into flocculent or flaky forms, or inorganic matter may not be fully dissociated, making it difficult to completely remove impurities during subsequent screening. Residual impurities can lead to problems such as "black heart" (unpleasant odor), low strength, and poor durability in recycled products, seriously affecting the application performance of recycled building materials. Second, high energy consumption and high carbon emissions. Traditional recycled aggregate reinforcement often uses "high-temperature calcination + rapid cooling" or "autoclaving" processes. The calcination temperature is usually above 1000℃, and the calcination time is long, resulting in extremely high energy consumption. In addition, the waste heat and exhaust gas generated during the calcination process are not effectively utilized, which does not meet the requirements of the "dual carbon" target. Third, surface and performance defects. Artificial aggregates prepared from fine powder of construction waste often have high porosity, high water absorption, and low compressive strength, making it difficult to meet the requirements of high-grade concrete or high-quality blocks.
[0004] To address the aforementioned technical challenges, industry researchers are exploring improvement methods. The production of non-sintered or low-temperature sintered recycled bricks has become a major research focus, aiming to reduce energy consumption and simplify the process. However, how to achieve efficient separation, low-energy solidification, and waste gas recycling of construction waste while ensuring the strength and durability of recycled bricks remains a technical challenge that has yet to be effectively resolved. Summary of the Invention
[0005] The purpose of this invention is to propose a low-carbon recycled brick and its preparation method, which solves the problems of difficult removal of organic matter from decoration waste, low strength of recycled aggregate, high energy consumption, and large carbon emissions, and realizes efficient resource utilization and low-carbon green production of decoration waste.
[0006] To achieve the above objectives, this invention proposes a low-carbon recycled brick, comprising the following raw materials by weight percentage: 50-60% recycled sand powder from construction waste, 25-35% recycled sand powder from waste concrete, and 15% laser-sintered artificial aggregate; the particle size of the recycled sand powder from construction waste is 0.1-2.36 mm, and the impurity content is controlled below 2%. Furthermore, the raw materials include the following weight percentages: 55% recycled sand powder from construction waste, 30% recycled sand powder from waste concrete, and 15% laser-sintered artificial aggregate; the mass ratio of the recycled sand powder from waste concrete to the artificial aggregate is 3:7.
[0007] This invention also proposes a method for preparing low-carbon recycled bricks, wherein the laser-sintered artificial aggregate is prepared by the following method: S1: The construction waste is crushed in the first stage using a toothed roller crusher and then screened to remove impurities, resulting in primary inorganic materials. S2: The primary inorganic material is crushed and screened to remove impurities using a flat roller crusher with a roller spacing of less than 8mm to obtain recycled sand powder. S3: The recycled sand powder is pressed into artificial aggregate raw material balls using a grooved roller press; S4: Use a green electric laser to sinter the surface of artificial aggregate raw material balls, and control the laser spot temperature at 1200-1400℃. S5: The artificial aggregate is calcined at low temperature using a calcination pipe constructed with a Fresnel prism, with the calcination temperature controlled at 600-800℃. S6: Mix the prepared artificial aggregate with recycled sand powder from waste concrete. The particle size of the recycled sand powder from waste concrete is 0.1-2.36mm, and the mass ratio of the recycled sand powder to the artificial aggregate is 3:7 to 5:5. Press the mixture into recycled brick blanks, and control the molding pressure at 30-80MPa. S7: The waste gas collected during the calcination process is introduced into the brick blank for carbonization curing. The carbonization curing temperature is 40-80℃ and the curing time is 12-48h to obtain the low-carbon recycled brick.
[0008] Furthermore, the toothed roller crusher has a toothed roller rotation speed of 150-250 r / min, a toothed roller diameter of 500-800 mm, and a tooth pitch of 30-50 mm.
[0009] Furthermore, the laser has a power of 2-5kW, a scanning speed of 50-150mm / s, and a spot diameter of 3-8mm; the Fresnel prism has a focusing magnification of 20-50 times and a calcination time of 15-40min.
[0010] Furthermore, the carbonization curing temperature is 50-70℃, the curing time is 20-30h, and the CO2 concentration in the exhaust gas is not less than 60%.
[0011] Compared with the prior art, the advantages of the present invention are: 1. This invention achieves efficient separation of organic and inorganic materials in construction waste through a combination of toothed roller crusher and flat roller crusher, significantly reducing the impurity content of recycled sand powder. The brittle inorganic materials in construction waste are effectively crushed into sand powder, while the flexible organic materials (such as wood strips, plastics, and cloth) remain in their original shape or are torn into larger pieces, greatly reducing the difficulty of "screening and impurity removal".
[0012] 2. This invention uses a green electric laser for surface sintering, which melts only the surface of the aggregate, resulting in energy consumption far lower than that of the overall sintering process. 3. This invention utilizes Fresnel prisms to calcine pipes to achieve low-temperature solar calcine, reducing fossil energy consumption; calcine waste gas is recovered for carbonization curing, realizing "waste treatment with waste", and the carbon emissions of the entire process are close to zero or even negative.
[0013] 4. The recycled bricks produced by this invention have a significant low-carbon label, and their various performance indicators meet the requirements for use in high-grade concrete and quality blocks. Attached Figure Description
[0014] Figure 1 This is a structural diagram of the actual product of the low-carbon recycled brick in Embodiment 1 of the present invention. Detailed Implementation
[0015] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be further described below.
[0016] Example 1 like Figure 1 As shown, this embodiment of a low-carbon recycled brick includes the following raw materials by weight percentage: 55% recycled sand powder from construction waste, 30% recycled sand powder from waste concrete, and 15% laser-sintered artificial aggregate.
[0017] The particle size of the recycled sand powder from the construction waste is 0.1-2.36 mm, and the impurity content is controlled below 1.5%.
[0018] This embodiment describes a method for preparing low-carbon recycled bricks, comprising the following steps: S1: The construction waste is crushed in the first stage using a toothed roller crusher. The toothed roller speed is 180r / min, the toothed roller diameter is 600mm, and the tooth pitch is 40mm. After crushing, it is screened through a 10mm screen to obtain primary inorganic materials. Among them, brittle inorganic materials are crushed into smaller particles, while flexible organic materials remain in their original shape or are torn into larger pieces. Preliminary separation is achieved through screening. S2: The primary inorganic material is subjected to secondary crushing using a flat roller crusher with a roller spacing of 6mm. The roller speed is 140r / min and the roller diameter is 500mm. After crushing, it is screened through a 2mm screen to remove impurities and residual organic matter, thus obtaining recycled sand powder from construction waste. S3: The recycled sand powder is pressed into artificial aggregate raw material balls using a grooved roller press. The groove depth of the roller surface is 5mm, the groove width is 8mm, and the pressing pressure is 20MPa. S4: A green electric laser is used to sinter the surface of the artificial aggregate raw material balls. The laser power is 3kW, the scanning speed is 100mm / s, the spot diameter is 5mm, and the laser spot temperature is controlled at 1300℃, so that the surface of the artificial aggregate is instantly heated to a molten state to form a dense shell. S5: The artificial aggregate is calcined at low temperature using a calcination pipe constructed with a Fresnel prism. The Fresnel prism has a focusing magnification of 35x, the calcination temperature is controlled at 700℃, and the calcination time is 25min. This process strengthens the internal structure of the artificial aggregate and removes residual organic impurities, while also collecting the waste gas generated during the calcination process. S6: Mix the artificial aggregate prepared in step (5) with recycled sand powder from waste concrete. The particle size of the recycled sand powder from waste concrete is 0.1-2.36 mm, and the mass ratio with the artificial aggregate is 3:7. Press it into recycled brick blanks, and control the molding pressure at 50 MPa. S7: The calcination waste gas collected in step (5) is passed into the brick blank pressed in step (6) for carbonization curing. The carbonization curing temperature is 60℃ and the curing time is 24h. The CO2 concentration in the waste gas is not less than 65%.
[0019] Example 2 This embodiment of a low-carbon recycled brick includes the following raw materials by weight percentage: 50g recycled sand powder from construction waste, 35g recycled sand powder from waste concrete, and 15g laser-sintered artificial aggregate.
[0020] The particle size of the recycled sand powder from the construction waste is 0.1-2.36 mm, and the impurity content is controlled below 1.2%.
[0021] This embodiment describes a method for preparing low-carbon recycled bricks, comprising the following steps: S1: The construction waste is crushed in the first stage using a toothed roller crusher with a toothed roller speed of 200r / min, a toothed roller diameter of 700mm, and a tooth pitch of 35mm. After crushing, it is screened through a 12mm screen to obtain primary inorganic materials. S2: The primary inorganic material is subjected to secondary crushing using a flat roller crusher with a roller spacing of 5mm. The roller speed is 160r / min and the roller diameter is 550mm. After crushing, it is screened through a 1.5mm screen to remove impurities and obtain recycled sand powder from construction waste. S3: The recycled sand powder is pressed into artificial aggregate raw material balls using a grooved roller press. The groove depth of the roller surface is 6mm, the groove width is 10mm, and the pressing pressure is 22MPa. S4: A green electric laser is used to sinter the surface of artificial aggregate raw material balls. The laser power is 4kW, the scanning speed is 80mm / s, the spot diameter is 6mm, and the laser spot temperature is controlled at 1350℃. S5: The artificial aggregate is calcined at low temperature using a calcination pipe constructed with a Fresnel prism. The Fresnel prism has a focusing magnification of 40x, the calcination temperature is controlled at 750℃, the calcination time is 30min, and the waste gas is collected. S6: Mix artificial aggregate with recycled sand powder from waste concrete at a mass ratio of 3.5:6.5, press into recycled brick blanks, and control the molding pressure at 55MPa; S7: The calcination exhaust gas is introduced into the brick blank for carbonization curing. The carbonization curing temperature is 70℃, the curing time is 30h, and the CO2 concentration in the exhaust gas is not less than 70%.
[0022] Example 3 This embodiment of a low-carbon recycled brick includes the following raw materials by weight percentage: 60g recycled sand powder from construction waste, 25g recycled sand powder from waste concrete, and 15g laser-sintered artificial aggregate.
[0023] The particle size of the recycled sand powder from the construction waste is 0.1-2.36 mm, and the impurity content is controlled below 1.8%.
[0024] This embodiment describes a method for preparing low-carbon recycled bricks, comprising the following steps: S1: The construction waste is crushed in the first stage using a toothed roller crusher. The toothed roller speed is 160r / min, the toothed roller diameter is 550mm, and the tooth pitch is 45mm. After crushing, it is screened through an 8mm screen to obtain primary inorganic materials. S2: The primary inorganic material is subjected to secondary crushing using a flat roller crusher with a roller spacing of 7mm. The roller speed is 120r / min and the roller diameter is 450mm. After crushing, it is screened again through a 2.5mm screen to remove impurities, thus obtaining recycled sand powder from construction waste. S3: The recycled sand powder is pressed into artificial aggregate raw material balls using a grooved roller press. The groove depth of the roller surface is 4mm, the groove width is 6mm, and the pressing pressure is 18MPa. S4: A green electric laser is used to sinter the surface of artificial aggregate raw material balls. The laser power is 2.5kW, the scanning speed is 120mm / s, the spot diameter is 4mm, and the laser spot temperature is controlled at 1250℃. S5: The artificial aggregate is calcined at low temperature using a calcination pipe constructed with a Fresnel prism. The Fresnel prism has a focusing magnification of 25x, the calcination temperature is controlled at 650℃, the calcination time is 20min, and the waste gas is collected. S6: Mix artificial aggregate with recycled sand powder from waste concrete at a mass ratio of 2.5:7.5, press into recycled brick blanks, and control the molding pressure at 45MPa; S7: The calcination exhaust gas is introduced into the brick blank for carbonization curing. The carbonization curing temperature is 50℃, the curing time is 20h, and the CO2 concentration in the exhaust gas is not less than 60%.
[0025] Example 4 This embodiment of a low-carbon recycled brick includes the following raw materials by weight percentage: 52% recycled sand powder from construction waste, 33% recycled sand powder from waste concrete, and 15% laser-sintered artificial aggregate.
[0026] The particle size of the recycled sand powder from the construction waste is 0.1-2.36 mm, and the impurity content is controlled below 1.3%.
[0027] This embodiment describes a method for preparing low-carbon recycled bricks, comprising the following steps: S1: The construction waste is crushed in the first stage using a toothed roller crusher with a toothed roller speed of 190r / min, a toothed roller diameter of 650mm, and a tooth pitch of 38mm. After crushing, it is screened through an 11mm screen to obtain primary inorganic materials. S2: The primary inorganic material is subjected to secondary crushing using a flat roller crusher with a roller spacing of 6mm. The roller speed is 150r / min and the roller diameter is 520mm. After crushing, it is screened again through a 1.8mm screen to remove impurities, thus obtaining recycled sand powder from construction waste. S3: The recycled sand powder is pressed into artificial aggregate raw material balls using a grooved roller press. The groove depth of the roller surface is 5.5mm, the groove width is 9mm, and the pressing pressure is 21MPa. S4: A green electric laser is used to sinter the surface of artificial aggregate raw material balls. The laser power is 3.5kW, the scanning speed is 90mm / s, the spot diameter is 5.5mm, and the laser spot temperature is controlled at 1320℃. S5: The artificial aggregate is calcined at low temperature using a calcination pipe constructed with a Fresnel prism. The Fresnel prism has a focusing magnification of 38x, the calcination temperature is controlled at 720℃, the calcination time is 28min, and the waste gas is collected. S6: Mix artificial aggregate with recycled sand powder from waste concrete at a mass ratio of 3.3:6.7, press it into recycled brick blanks, and control the molding pressure at 52MPa; S7: The calcination exhaust gas is introduced into the brick blank for carbonization curing. The carbonization curing temperature is 65℃, the curing time is 26h, and the CO2 concentration in the exhaust gas is not less than 68%.
[0028] Performance parameters of the recycled bricks of this invention: To illustrate the effectiveness of the present invention, the performance of the recycled bricks prepared in Examples 1, 2, 3, and 4 was tested, and the results are shown in Table 1: Table 1 Performance of each group of recycled bricks
[0029] Bulk density / g·cm⁻³ 2.15 2.22 2.08 2.18 Water absorption rate / % 8.5 6.8 10.2 7.9 Cylinder compressive strength / MPa 28.5 32.6 24.8 30.2 Flexural strength / MPa 6.2 7.5 5.4 6.8 Compressive strength / MPa 45.8 52.3 38.6 48.5 Carbonization depth / mm 2.1 1.8 2.5 2.0 Softening coefficient 0.92 0.95 0.88 0.93 Abrasion resistance / cm³ 0.35 0.28 0.42 0.32
[0030] As shown in Table 1, the bulk density of the recycled bricks of this invention is ≥2.08 g / cm³. 3 The water absorption rate is ≤10.2%, the compressive strength is ≥24.8MPa, the flexural strength is ≥5.4MPa, and the compressive strength is ≥38.6MPa. All performance indicators meet the requirements for use in high-grade concrete and high-quality blocks.
[0031] Further analysis shows that this invention achieves efficient separation of organic and inorganic matter in construction waste through a graded combination of toothed roller crushing and flat roller crushing, controlling the impurity content of recycled sand powder to below 1.8%; it uses a green electric laser for surface sintering, which only momentarily heats the aggregate surface to a molten state to form a dense glassy shell, resulting in energy consumption far lower than traditional integral sintering processes; it utilizes Fresnel prism calcination pipes to achieve low-temperature solar calcination (600-800℃), significantly reducing fossil energy consumption; the calcination exhaust gas is rich in CO2, which is recovered for carbonization curing, achieving "waste treatment with waste," and the carbon emissions of the entire process are close to zero or even negative.
[0032] This invention solves the problems of difficult organic matter removal from construction waste, low strength of recycled aggregates, high energy consumption, and high carbon emissions by combining graded crushing and separation, laser surface sintering, and low-temperature calcination. It achieves efficient resource utilization and low-carbon green production of construction waste. The resulting recycled bricks have a significant low-carbon label, and their performance indicators meet the requirements for high-grade concrete and quality blocks.
[0033] The above are merely preferred embodiments of the present invention and do not constitute any limitation on the present invention. Any equivalent substitutions or modifications made by those skilled in the art to the technical solutions and content disclosed in the present invention without departing from the scope of the present invention shall be deemed to have remained within the scope of protection of the present invention.
Claims
1. A low-carbon recycled brick, characterized in that, The raw materials include the following weight percentages: 50-60% recycled sand powder from construction waste, 25-35% recycled sand powder from waste concrete, and 15% laser-sintered artificial aggregate; the particle size of the recycled sand powder from construction waste is 0.1-2.36mm, and the impurity content is controlled below 2%.
2. The low-carbon recycled brick according to claim 1, characterized in that, The raw materials include the following weight percentages: 55% recycled sand powder from construction waste, 30% recycled sand powder from waste concrete, and 15% laser-sintered artificial aggregate; the mass ratio of the recycled sand powder from waste concrete to the artificial aggregate is 3:
7.
3. A method for preparing low-carbon recycled bricks, wherein the laser-sintered artificial aggregate is prepared by the following method: S1: The construction waste is crushed in the first stage using a toothed roller crusher and then screened to remove impurities, resulting in primary inorganic materials. S2: The primary inorganic material is crushed and screened to remove impurities using a flat roller crusher with a roller spacing of less than 8mm to obtain recycled sand powder. S3: The recycled sand powder is pressed into artificial aggregate raw material balls using a grooved roller press; S4: Use a green electric laser to sinter the surface of artificial aggregate raw material balls, and control the laser spot temperature at 1200-1400℃. S5: The artificial aggregate is calcined at low temperature using a calcination pipe constructed with a Fresnel prism, with the calcination temperature controlled at 600-800℃. S6: Mix the prepared artificial aggregate with recycled sand powder from waste concrete. The particle size of the recycled sand powder from waste concrete is 0.1-2.36mm, and the mass ratio of the recycled sand powder to the artificial aggregate is 3:7 to 5:
5. Press the mixture into recycled brick blanks, and control the molding pressure at 30-80MPa. S7: The waste gas collected during the calcination process is introduced into the brick blank for carbonization curing. The carbonization curing temperature is 40-80℃ and the curing time is 12-48h to obtain the low-carbon recycled brick.
4. The method for preparing low-carbon recycled bricks according to claim 3, characterized in that: The toothed roller crusher has a toothed roller rotation speed of 150-250 r / min, a toothed roller diameter of 500-800 mm, and a tooth pitch of 30-50 mm.
5. The method for preparing low-carbon recycled bricks according to claim 1, characterized in that: The laser has a power of 2-5kW, a scanning speed of 50-150mm / s, and a spot diameter of 3-8mm; the Fresnel prism has a focusing magnification of 20-50 times and a calcination time of 15-40min.
6. The low-carbon recycled brick and its preparation method according to claim 1, characterized in that: The carbonization curing temperature is 50-70℃, the curing time is 20-30h, and the CO2 concentration in the exhaust gas is not less than 60%.